Optimized Loading of Carboxymethyl Cellulose (CMC) in Tri-component Electrospun Nanofibers Having Uniform Morphology - Hashmi, Motahira (Polymers (Basel), 2020)
Cellulose is one of the most hydrophilic polymers with sufficient water holding capacity but it is unstable in aqueous conditions and it swells. Cellulose itself is not suitable for electrospun nanofibers’ formation due to high swelling, viscosity, and lower conductivity. Carboxymethyl cellulose (CMC) is also super hydrophilic polymer, however it has the same trend for nanofibers formation as that of cellulose. Due to the above-stated reasons, applications of CMC are quite limited in nanotechnology. In recent research, loading of CMC was optimized for electrospun tri-component polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and carboxymethyl cellulose (CMC) nanofibers aim at widening its area of applications. PVA is a water-soluble polymer with a wide range of applications in water filtration, biomedical, and environmental engineering, and with the advantage of easy process ability. However, it was observed that only PVA was not sufficient to produce PVA/CMC nanofibers via electrospinning. To increase spinnability of PVA/CMC nanofibers, PVP was selected as the best available option because of its higher conductivity and water solubility. Weight ratios of CMC and PVP were optimized to produce uniform nanofibers with continuous production as well. It was observed that at a weight ratio of PVP 12 and CMC 3 was at the highest possible loading to produce smooth nanofibers.